2016
DOI: 10.3892/br.2016.686
|View full text |Cite
|
Sign up to set email alerts
|

Urinary volatile organic compounds as potential biomarkers for renal cell carcinoma

Abstract: Currently, there is no adequate, sensitive, reproducible, specific and noninvasive biomarker that can reliably be used to detect renal cell carcinoma (RCC). Previous studies have elucidated the urinary non-volatile metabolic profile of RCC. However, whether urinary volatile organic compound (VOC) profiles are able to identify RCC remains to be elucidated. In the present study, urine was collected from 22 patients with RCC and 25 healthy subjects. Principal component analysis and orthogonal partial least square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 23 publications
6
31
2
Order By: Relevance
“…Our findings are different from the results of another unique similar study described until now in the literature which detected statistically significant differences in 14 VOCs in RCC patients compared to controls. These differences could at least in part be dependent on differences in samples’ preparation (we used acidified urine samples) and the extraction procedure used, as the type of fibre.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings are different from the results of another unique similar study described until now in the literature which detected statistically significant differences in 14 VOCs in RCC patients compared to controls. These differences could at least in part be dependent on differences in samples’ preparation (we used acidified urine samples) and the extraction procedure used, as the type of fibre.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the volatile profile of human urine was studied, in an attempt to reveal a VOC‐biomarker panel for non‐invasive detection of this cancer. Despite the potential of VOCs for the discrimination between cancer and control samples being currently acknowledged , concerning RCC, the potentialities of human urine volatilome for that purpose are scarcely exploited .…”
Section: Discussionmentioning
confidence: 99%
“…As a developing novel tool for the non-invasive detection of various disease states in recent years, VOC analysis has been applied in different body fluids, such as blood, urine, and saliva [12][13][14][15]. VOC analysis is important in the diagnosis of respiratory infections as an accurate and rapid method and has clinical value in guiding the use of antibiotics [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, gas chromatography-mass spectrometry (GC-MS) is a preferred method for the identification of pathogen markers with an appropriate sensitivity [11]. As a developing novel tool for non-invasive detection of various disease states in recent years, VOC analysis has been applied in different body fluids, such as blood, urine, and saliva [12][13][14][15], and it also can be applied to identify pathogens such as Escherichia coli, Staphylococcus aureus, Mycobacterium tuberculosis, Haemophilus influenzae, Streptococcus pneumoniae, rhinoviruses, influenza A virus and others [9,10,16]. Although there are a large number of clinical studies on the diagnosis of CNS infection such as cellular and chemistry parameters in CSF, conventional culture for bacteria and PCR with sequencing for viral [3,17] studies on the VOCs in the CSF have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of volatile organic compounds (VOC) in exhaled breath is a potential strategy for non-invasive POC diagnosis or exclusion of bacterial infection. To date, analysis of VOCs in human excretions suggests a potential role in the diagnosis of cancers [ 5 7 ], inflammatory bowel disease [ 8 ], gastric [ 9 ] and respiratory infections in chronic obstructive pulmonary disease [ 10 ], cystic fibrosis [ 11 ], and for the diagnosis of ventilator-associated pneumonia (VAP) [ 12 ], amongst other entities. No study has attempted to identify VOC signatures associated with bacterial infection in an unselected population presenting with RTI.…”
Section: Introductionmentioning
confidence: 99%